RAINWATER HARVESTING SYSTEM’S UTILIZATION FOR DOMESTIC WATER NEEDS IN KOBANGO II HAMLET, BANTUL REGENCY - Dian Hudawan Santoso,; Rahmawati, Berty Dwi (Malaysian Journal of Science, 2022)
Limited groundwater, especially during the dry season, poses a challenge for Kobango II Hamlet Bantul Regency residents to have sufficient clean water supply for their daily needs. Inadequate aquifer conditions and the inability to release enough water are reasons for clean water scarcity. Thus, this study aims to determine the effectiveness of using the rainwater harvesting (RWH) system for domestic water needs in the Kobango II Hamlet Bantul Regency. The method used in this research is conducting a survey, observation, quantitative analysis of secondary data using rainfall data and aquifer conditions and calculating RWH system requirements. The results obtained from this research demonstrated that the required diameter of the vertical gutter for the RWH system is 6.65 cm and the diameter of the gutter is 0.056 cm.